A study on the awareness and practice of medical education technologies among medical college teachers - Saju, C. R.; Vincent, Jose; Joshy, Vidhu M. (International Journal of Research in Medical Sciences, 2019)
Background: Globally there is a move to reorient the medical education to suit the needs of the developing nations. Medical Council of India has made it is mandatory that all faculty need to attend Basic course in Medical Education Technologies (MET) to improve teaching effectiveness. In spite of their efforts in this regard many of the faculty is still unaware of this initiative and those who have already attended the course are not effectively practicing it. This study aimed at assessing level of awareness and practice of medical education technologies among the teaching faculty. Methods: Data was collected from the faculty by personal interviews using a validated semi-structured questionnaire and analysed using SPSS. Results: 219 faculty members participated in the study working in 26 departments. Mean age of faculty was 40.98 (SD: 12.36). 57.1% of them were males and 42.9% were females. The level of awareness among study participants about learning process related medical education technologies ranged from 57% (for psychomotor domain) to 74% (for setting up of educational objectives). The awareness and practice of ‘teaching process’ and assessment process related medical education technologies remained low. No statistically significant association was obtained between awareness and practice of SLO, Microteaching, and MiniCEX. Conclusions: Majority of teachers remain untrained in the medical education technologies at the time of the study. Of the non-clinical compared to the clinical stream of teachers, greater proportion of teachers in non-clinical section have been trained. The awareness and practice of ‘medical education technologies’ remain low among the study participants.